Small Brain Lesion Enhancement and Gadolinium Deposition in the Rat Brain: Comparison Between Gadopiclenol and Gadobenate Dimeglumine. Issue 2 (February 2022) - Violas, Xavier; Rasschaert, Marlène; Santus, Robin; Factor, Cécile; Corot, Claire; Catoen, Sarah; Idée, Jean-Marc; Robert, Philippe
Abstract : Objectives: The aim of the set of studies was to compare gadopiclenol, a new high relaxivity gadolinium (Gd)–based contrast agent (GBCA) to gadobenate dimeglumine in terms of small brain lesion enhancement and Gd retention, including T1 enhancement in the cerebellum. Materials and Methods: In a first study, T1 enhancement at 0.1 mmol/kg body weight (bw) of gadopiclenol or gadobenate dimeglumine was evaluated in a small brain lesions rat model at 2.35 T. The 2 GBCAs were injected in an alternated and cross-over manner separated by an interval of 4.4 ± 1.0 hours (minimum, 3.5 hours; maximum, 6.1 hours; n = 6). In a second study, the passage of the GBCAs into cerebrospinal fluid (CSF) was evaluated by measuring the fourth ventricle T1 enhancement in healthy rats at 4.7 T over 23 minutes after a single intravenous (IV) injection of 1.2 mmol/kg bw of gadopiclenol or gadobenate dimeglumine (n = 6/group). In a third study, Gd retention at 1 month was evaluated in healthy rats who had received 20 IV injections of 1 of the 2 GBCAs (0.6 mmol/kg bw) or a similar volume of saline (n = 10/group) over 5 weeks. T1 enhancement of the deep cerebellar nuclei (DCN) was assessed by T1-weighted magnetic resonance imaging at 2.35 T, performed before the injection and thereafter once a week up to 1 month after the last injection. Elemental Gd levels in central nervous system structures, in muscle and in plasma were determined by inductively coupled plasma mass spectrometry (ICP-MS) 1 month after the last injection. Results: The first study in a small brain lesion rat model showed a ≈2-fold higher number of enhanced voxels in lesions with gadopiclenol compared with gadobenate dimeglumine. T1 enhancement of the fourth ventricle was observed in the first minutes after a single IV injection of gadopiclenol or gadobenate dimeglumine (study 2), resulting, in the case of gadopiclenol, in transient enhancement during the injection period of the repeated administrations study (study 3). In terms of Gd retention, T1 enhancement of the DCN was noted in the gadobenate dimeglumine group during the month after the injection period. No such enhancement of the DCN was observed in the gadopiclenol group. Gadolinium concentrations 1 month after the injection period in the gadopiclenol group were slightly increased in plasma and lower by a factor of 2 to 3 in the CNS structures and muscles, compared with gadobenate dimeglumine. Conclusions: In the small brain lesion rat model, gadopiclenol provides significantly higher enhancement of brain lesions compared with gadobentate dimeglumine at the same dose. After repeated IV injections, as expected for a macrocyclic GBCA, Gd retention is minimalized in the case of gadopiclenol compared with gadobenate dimeglumine, resulting in no T1 hypersignal in the DCN.